Institutional Economics as Theory of Policy Change: Impact of Past Policy Failures on Present Policy. Issue 1 (2nd January 2018) - Noda, Koji
Abstract: Social scientists have developed several theories for understanding or evaluating policy change over time. Since all costs or benefits are not internalized owing to positive transaction costs, policymaking is always implemented under cost underestimation conditions and, therefore, is imperfect. I call this trait policy failure in this article. Furthermore, I show that a new framework combining the social costs approach and the legal/economic approach in institutional economics is suitable and can be applied to evaluating how past policy failures affect present policy, providing as an example the Fukushima nuclear disaster in Japan.